Communion with the Triune God - Owen, John, 1616-1683; Kapic, Kelly M., 1972-; Taylor, Justin, 1976- (Wheaton, Illinois Crossway Books, 2007)
Rev. ed of: Of communion with God the Father, Son and Holy Ghost, each person distinctly in love, grace, and consolation.
Includes indexes
Keywords: Spirituality